Estimates of seasonal influenza‐associated mortality in Bangladesh, 2010‐2012 - Ahmed, Makhdum (Influenza Other Respir Viruses, 2017)
BACKGROUND: Seasonal influenza‐associated mortality estimates help identify the burden of disease and assess the value of public health interventions such as annual influenza immunization. Vital registration is limited in Bangladesh making it difficult to estimate seasonal influenza mortality. OBJECTIVES: Our study aimed to estimate seasonal influenza‐associated mortality rates for 2010‐2012 in Bangladesh. METHODS: We conducted surveillance among hospitalized patients with severe acute respiratory illness (SARI) for persons aged ≥5 years and severe pneumonia for children <5 years in 11 sites across Bangladesh. We defined the catchment areas of these sites and conducted a community survey in 22 randomly selected unions (administrative units) within the catchment areas to identify respiratory deaths. We multiplied the proportion of influenza‐positive patients at our surveillance sites by the age‐specific number of respiratory deaths identified to estimate seasonal influenza‐associated mortality. RESULTS: Among 4221 surveillance case‐patients, 553 (13%) were positive for influenza viruses. Concurrently, we identified 1191 persons who died within 2 weeks of developing an acute respiratory illness within the catchment areas of the surveillance hospitals. In 2010‐2011, the estimated influenza‐associated mortality rate was 6 (95% CI 4‐9) per 100 000 for children <5 years and 41 (95% CI 35‐47) per 100 000 for persons >60 years. During 2011‐2012, the estimated influenza‐associated mortality rate was 13 (95% CI 10‐16) per 100 000 among children <5 years and 88 (95% CI 79‐98) per 100 000 among persons aged >60 years. CONCLUSIONS: We identified a substantial burden of influenza‐associated deaths in Bangladesh suggesting that the introduction of prevention and control measures including seasonal vaccination should be considered by local public health decision‐makers.